Managing service potentiality of small urban centers case study: City of Sardasht, south east of Iran - Farjam Rasoul (Journal of Urban Management, 2017)
Many exist regions, define as deprived region. These regions must be managed by small urban regional center as regional focal points from the perspective of territorial urban development. Urban and regional development management could not be a very complicated issue while small urban regional centers have their historical, social and economic process. The problem starts, whenever, political interventions come in. Sardasht focal point has had the same story and upgraded to a city through a political declaration in 2010. It is the first urban center of Bashagard area in Hormozgan province which is located in southeast of Iran. The declaration was made to create service center to enhance development process in the area. The declaration also created centralization of essential services thereby facilitating the delivery of basic services to the people of the region. Main purpose of the article is to measure current and future role and potential of Sardasht city as a regional market town in Bashagard deprived region. In this article, the existing practices in the delivery of services in the region were analyzed to determine the role Sardasht market and the factors affecting the delivery of services as viewed by the inhabitants of rural hinterlands in the region. Two major objectives raised in the survey are capability of Sardasht city to deliver basic services to the people and the facilities are needed to be established in the town to regulate the delivery of services from the city to the surrounding areas. Data collection was done in two ways. The first one was librarian method (including statistical data of population census and residents and identity certificate of village.The second one was questionnaire research. These methods were used to obtain quantitative data set. The data provided essential index for determining the importance of relationships between Sardasht market-town and residents of its rural hinterland. In order to determine the essential statistical population, three objects were studied simultaneously (the potential of Bashagard rural residents, the geographic distribution of Bashagard villages and different levels of their services). The selected villages for questionnaire survey were 51 and the number of residents that have been questioned ware about 248, which has assessed by Cochran method. Finding showed that those services which are more important in role fulfillment of Sardasht market-town include: sanitation house, health, remedial centers, drugstore, dentistry, high school, pre-university, library, transportation, trading agricultural instrument, referring to the banks, foodstuff and nonfood stuffs stores, post office and telecommunication, referring to official & disciplinary centers, medical services, veterinary. And to some extent farming instruments markets doesn’t affect role fulfillment so it should be focused by those locals in charge. Also the results showed that three settlements, Khomeinishahr, Jakdan and Goharan are going to continue the role fulfillment of Sardasht market- town.